Long-term results and risk factor analysis for recurrence after curative endoscopic therapy in 349 patients with high-grade intraepithelial neoplasia and mucosal adenocarcinoma in Barrett's oesophagus. Issue 9 (6th May 2008) - Pech, O; Behrens, A; May, A; Nachbar, L; Gossner, L; Rabenstein, T; Manner, H; Guenter, E; Huijsmans, J; Vieth, M; Stolte, M; Ell, C
Abstract : Objective: Endoscopic therapy is increasingly being used in the treatment of high-grade intraepithelial neoplasia (HGIN) and mucosal adenocarcinoma (BC) in patients with Barrett's oesophagus. This report provides 5 year follow-up data from a large prospective study investigating the efficacy and safety of endoscopic treatment in these patients and analysing risk factors for recurrence. Design: Prospective case series. Setting: Academic tertiary care centre. Patients: Between October 1996 and September 2002, 61 patients with HGIN and 288 with BC were included (173 with short-segment and 176 with long-segment Barrett's oesophagus) from a total of 486 patients presenting with Barrett's neoplasia. Patients with submucosal or more advanced cancer were excluded. Interventions: Endoscopic therapy. Main outcome measures: Rate of complete remission and recurrence rate, tumour-associated death. Results: Endoscopic resection was performed in 279 patients, photodynamic therapy in 55, and both procedures in 13; two patients received argon plasma coagulation. The mean follow-up period was 63.6 (SD 23.1) months. Complete response (CR) was achieved in 337 patients (96.6%); surgery was necessary in 13 (3.7%) after endoscopic therapy failed. Metachronous lesions developed during the follow-up in 74 patients (21.5%); 56 died of concomitant disease, but none died of BC. The calculated 5 year survival rate was 84%. The risk factors most frequently associated with recurrence were piecemeal resection, long-segment Barrett's oesophagus, no ablative therapy of Barrett's oesophagus after CR, time until CR achieved >10 months and multifocal neoplasia. Conclusions: This study showed that endoscopic therapy was highly effective and safe, with an excellent long-term survival rate. The risk factors identified may help stratify patients who are at risk for recurrence and those requiring more intensified follow-up.